Two is the key to 14-3-3: dimeric mechanical signaling devices - MacKintosh, Carol (Henry Stewart Talks, 2010)
14-3-3s dock onto specific sites phosphorylated by AGC and CAMK kinases, 14-3-3s have hundreds of phosphoprotein partners, 14-3-3 dimers as mechanical levers and clamps, and 'coincidence detectors', Cellular regulation of the 14-3-3-binding phosphoproteome, Case studies including plant leaf responses to darkness and human cell responses to insulin